1993
DOI: 10.3758/bf03211715
|View full text |Cite
|
Sign up to set email alerts
|

Comparing decision bound and exemplar models of categorization

Abstract: The performance of a decision bound model of categorization (Ashby, 1992a; Ashby & Maddox, in press) is compared with the performance of two exemplar models. The first is the generalized context model (e.g., Nosofsky, 1986Nosofsky, , 1992 and the second is a recently proposed deterministic exemplar model (Ashby & Maddox, in press), which contains the generalized context model as a special case. When the exemplars from each category were normally distributed and the optimal decision bound was linear, the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
576
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(584 citation statements)
references
References 52 publications
8
576
0
Order By: Relevance
“…Thus, for the EBRW to roughly match the accuracy predictions yielded by the GCM, modifications in the values of some of the other free parameters would need to be made. It is interesting to note that Maddox and Ashby (1993) found that, when fitting the data of highly experienced individual participants, the GCM does underpredict the observed accuracies, so the EBRW may represent an improvement in this regard. We consider these issues in more depth in the General Discussion.…”
Section: Relations Among Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, for the EBRW to roughly match the accuracy predictions yielded by the GCM, modifications in the values of some of the other free parameters would need to be made. It is interesting to note that Maddox and Ashby (1993) found that, when fitting the data of highly experienced individual participants, the GCM does underpredict the observed accuracies, so the EBRW may represent an improvement in this regard. We consider these issues in more depth in the General Discussion.…”
Section: Relations Among Modelsmentioning
confidence: 97%
“…Indeed, Maddox and Ashby (1993) proposed an extended version of the GCM with precisely this type of response rule to allow the model to potentially account for the deterministic responding exhibited by highly experienced individual participants. ~° McKinley and Nosofsky (1995) found that this extended response rule yielded fits to Maddox and Ashby's (1993) data that were far better than those of the GCM and as good as important representatives from the class of decision boundary models. Thus, at least in situations in which models are fitted to individual-participant accuracy data from highly experienced observers, the EBRW appears to provide a major improvement over the GCM.…”
Section: Probabilistic Versus Deterministic Response Rules and Overalmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is not inconsistent with the hypothesis that the two different types of training result in different types of category representation, but it also suggests that the type of transfer trial influenced which representation participants appeared to be using. Using a psychologically plausible generalization of the original GCM (Maddox & Ashby, 1993;Nosofsky, Gluck, Palmeri, McKinley, & Glauthier, 1994) that has now become a standard part of the model, Kruschke, Johansen, and Blair (1999) showed that this standard exemplar model (detailed below) can reasonably account for all of Yamauchi and Markman's (1998) six conditions, as shown in Table 3. The added parameter indexes response confidence and specifies the degree to which a given difference in evidence for one response over another should translate into a difference in response probabilities.…”
mentioning
confidence: 99%
“…We review two different multivariate designs (shown in Figures 1C and 1E). Maddox and Ashby (1993) had participants classify rectangles that varied in two dimensions: height and width. Category membership was determined by assuming that each category was distributed over the height and width of the rectangles as an uncorrelated bivariate normal ( Figure 1C).…”
mentioning
confidence: 99%